2021
DOI: 10.1097/pr9.0000000000000898
|View full text |Cite
|
Sign up to set email alerts
|

From the low-density lipoprotein receptor–related protein 1 to neuropathic pain: a potentially novel target

Abstract: The low-density lipoprotein receptor–related protein 1 plays a major role in the regulation of neuroinflammation, neurodegeneration, neuroregeneration, neuropathic pain, and deficient cognitive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 137 publications
(363 reference statements)
0
13
0
Order By: Relevance
“…LPR1 has shown to be able to reduce inflammatory response by reducing the production of proinflammatory mediators through different signaling pathways (49). The involvement of LRP1 in FM is unknown, but it is tempting to speculate that the increase in this protein after exercise has a protective role in FM, as it potentially plays a role in modulating and regulating inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…LPR1 has shown to be able to reduce inflammatory response by reducing the production of proinflammatory mediators through different signaling pathways (49). The involvement of LRP1 in FM is unknown, but it is tempting to speculate that the increase in this protein after exercise has a protective role in FM, as it potentially plays a role in modulating and regulating inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…23 Although the loss of LRP1 function appears to promote inflammation and neuropathic pain, it is not known whether the gain of LRP1 activation alleviate nociceptive and neuropathic pain states. 24 Herein, we identify SP16 as a significant regulator of acute nociceptive, inflammatory, and neuropathic pain. SP16 replicated the neurite extension activity previously shown by other LRP1 agonists.…”
Section: Introductionmentioning
confidence: 99%
“…In Schwann cells (SC), genetic deletion of LRP1 increases the extent and magnitude of neuropathic pain before and after injury 23 . Although the loss of LRP1 function appears to promote inflammation and neuropathic pain, it is not known whether the gain of LRP1 activation alleviate nociceptive and neuropathic pain states 24 …”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that activation of LDL receptor-related protein 1 (LRP-1) can indirectly reduce neuropathic pain by attenuation of inflammation, reporting better outcomes for neuropathies such as Alzheimer disease, nerve injury, and diabetic peripheral neuropathy. All these results suggest an extremely interesting therapeutic target of the mechanism of PRF on ZAP [ 22 ].…”
Section: Discussionmentioning
confidence: 99%